1983
DOI: 10.1007/bf01923196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute vagally-mediated bradycardia on systemic hemodynamics and coronary blood flow before and after coronary stenosis

Abstract: The effects of short episodes (1 min) of vagally-mediated bradycardia were studied in 9 anesthetized dogs utilizing vagal stimulation and slow atrial pacing (120 and 80 beats/min) before and after graded coronary constriction of the left anterior descending (LAD) and the left circumflex (CCA). In the presence of 90% LAD stenosis, bradycardia tended to restore both the elevated total LAD coronary vascular resistance (CVR-LAD) and the reduced, total CVR-CCA towards control levels obtained at corresponding slow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…As previously mentioned, these data strongly suggest that vagally mediated reductions in myocardial electrical impedance occurred secondary to heart rate‐dependent reductions in cardiac metabolic demand. Although these results are in agreement with previous observations on the vagal influence during ischaemia (Senges et al 1983), it should be noted that dual‐chamber pacing (right atrium and right ventricle) was used to maintain heart rate during vagal stimulation (VAG/P group). The resulting atrioventricular synchronization could alter ventricular filling (stroke volume) or sympathovagal balance (Chiladakis et al 2004), thereby confounding the response to vagal nerve stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As previously mentioned, these data strongly suggest that vagally mediated reductions in myocardial electrical impedance occurred secondary to heart rate‐dependent reductions in cardiac metabolic demand. Although these results are in agreement with previous observations on the vagal influence during ischaemia (Senges et al 1983), it should be noted that dual‐chamber pacing (right atrium and right ventricle) was used to maintain heart rate during vagal stimulation (VAG/P group). The resulting atrioventricular synchronization could alter ventricular filling (stroke volume) or sympathovagal balance (Chiladakis et al 2004), thereby confounding the response to vagal nerve stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, and in agreement with the acute attenuation of the early ischaemic myocardial electrical impedance increase observed in the present study, vagal nerve stimulation has been shown to reduce myocardial energy demand and metabolic derangements during ischaemia (Senges et al 1983; Sammel et al 1983; Sidi et al 1995). For example, Sammel et al (1983) reported that, in addition to a potent anti‐arrhythmic effect, vagal stimulation during coronary occlusion reduced myocardial creatine kinase depletion, roughly in proportion to a reduction in the heart rate–blood pressure product.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation